Dinamika Money Politik Pada Pelaksanaan Pemilihan Umum Di Kabupaten Ponorogo - Ahmad Catur Adinugroho; Muhammad Oky Fauzi; Nanik Prasetyoningsih; Ferdin Okta Wardana (PERSPEKTIF, 2022)
This article aims to determine the factors that cause money politics in the general election in Ponorogo Regency, in addition to knowing how law enforcement is carried out by law enforcement officials against money politics in general elections and the appropriate regulations to overcome money politics. Problems with the factors that cause money in Ponorogo Regency, in addition to law enforcement carried out in general elections and appropriate regulations to overcome this. To approach these problems, empirical juridical research is used with a conceptual approach and the provisions of the law. Data collection was done by interview and observation and literature study. Data were collected and analyzed descriptively qualitatively by reducing data, displaying data and verifying data. This study concludes that the factors that cause money in the implementation of general elections in Ponorogo Regency are: the existence of tradition, community economic factors, lack of knowledge from the community and law enforcement that has not been optimal. Money politics law enforcement is regulated by Law Number 1 of 2015 concerning Supervision of Government Nets, replacing Law Number 1 of 2014 concerning the Election of Governors and Regents. Even though there are laws that regulate, money politics still happens. Therefore, to overcome this, it is necessary to evaluate the rules in elections..